Systematic Literature Review of Ocean Wave Renewable Energy - Nuryadi, Ari; Yendri Sudiar, Nofi; Hamdi (Journal of Climate Change Society, 2023)
Renewable energy is a concern to overcome the limitations of fossil energy, one type of renewable energy is ocean wave energy. There are various research topics related to the development of ocean wave energy potential carried out by countries in the world, for this reason the authors conducted a review related to journal papers that discuss ocean wave renewable energy. The method for this study used a Systematic Literature Review (SLR) on journal papers published from 2008-2023, a total of 44 journal papers. The three research questions contained in this study so as to obtain research results that the most countries that carry out research related to ocean wave renewable energy are China. There are a total of nine topics discussed related to ocean wave renewable energy with the most frequently discussed topic trends related to the utilization and modeling of ocean wave renewable energy.